Hubungan Antara Self Efficacy Dengan Kecemasan Menghadapi Masa Depan Para Penerima Manfaat di PPSA Taruna Yodha Sukoharjo - Khairi, Alfin Miftahul; Armianto, Dita Putri (Jurnal Bimbingan dan Konseling Islam, 2024)
The level of anxiety facing the future is related to worries related to uncertainty in the future. One of the factors that influence anxiety facing the future is self-efficacy. This study aims to determine and empirically test the relationship between self-efficacy and anxiety about the future of the beneficiaries at the Taruna Yodha Sukoharjo Children's Social Service Panti (PPSA). This research is a quantitative correlational type. The sample in this study were all beneficiaries of the Taruna Yodha Sukoharjo Children's Social Service Panti (PPSA) with a total of 35 beneficiaries (total sampling). The data collection technique used is using a questionnaire with a Likert Scale. The data obtained were then analyzed using descriptive and inverse statistics. The analysis technique using the analysis prerequisite test includes the normality test and linearity test. Hypothesis testing uses 2 tests, namely, the Pearson correlation test and the t-test. The results of the reliability test for the self-efficacy variable are 0.966 and the variable facing the future is 0.910. And the second variable is declared reliable because the significance value is > 0.05. The results showed that there was a real or significant relationship between self-efficacy and anxiety facing the future of the beneficiaries. It is known that the correlation value based on the correlation test results obtained a significance value of 0.012 which is positive, meaning that the significance value is 0.012 < 0.05. The hypothesis is accepted that the self-efficacy variable has a positive relationship with anxiety facing the future of the beneficiaries.